2019
DOI: 10.24071/jpsc.001794
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Particle Size, Extraction Time, and Solvent Selection on Daidzein Extracted Amount from Tempeh-A Fermented Product of Soybean

Abstract: Daidzein, one of the isoflavone aglycones contained in tempeh, has several biological activities such as anti-inflammatory, anti-oxidant, anti-breast cancer, and suppression of expression of matrix metalloprotease-9. As a fermented product from soybeans, daidzein content in tempeh was found in higher concentration compared to the soybean raw material. It was important to optimize several factors affecting extraction process such as particle size of tempeh simplicia, extraction time, and solvent in order to dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 14 publications
1
9
0
6
Order By: Relevance
“…In addition, the sample can be durable because removing the water content in the sample can facilitate the withdrawal of bioactive compounds during maceration (Cacique et al 2020). The sample was smoothed (Figure 1.D) to expand the touch surface and facilitate the maceration process, where the larger the surface area of the contact area with the solvent, the more effective the extraction process (TeGrotenhuis et al 1999;Yuliani et al 2019).…”
Section: Amethyst Leaf Extractmentioning
confidence: 99%
“…In addition, the sample can be durable because removing the water content in the sample can facilitate the withdrawal of bioactive compounds during maceration (Cacique et al 2020). The sample was smoothed (Figure 1.D) to expand the touch surface and facilitate the maceration process, where the larger the surface area of the contact area with the solvent, the more effective the extraction process (TeGrotenhuis et al 1999;Yuliani et al 2019).…”
Section: Amethyst Leaf Extractmentioning
confidence: 99%
“…Several Asian countries consume soybean products in various forms, including soymilk, tofu, tempeh, miso, soybean nuts, and others. Soybean products not only have been consumed as functional foods over the last two decades but also have been reported to provide several health benefits and cancer prevention. , Recently, researchers have become more interested in soybean isoflavones because of their beneficial effects in combating cancer. In earlier research, it has been shown that soybean foods possess naturally occurring soybean isoflavones, which are responsible for the biological activities; mainly genistein, daidzein, glycitein, and glucosides comprise the major soybean isoflavones. ,, Different soybean products have different levels of isoflavones because of their processing or production technique, as well as their extraction procedure. , …”
Section: Pharmacotherapeutic Effects Of Soybean Wastesmentioning
confidence: 99%
“…6,85,99 Different soybean products have different levels of isoflavones because of their processing or production technique, as well as their extraction procedure. 100,101 Researchers have shown that soybean isoflavones are effective in preventing cancer, preventing osteoporosis, decreasing antibacterial inflammation, and regulating heart disease. 95−98 Studies have shown dietary soybean consumption to be associated with decreased blood cholesterol, improved cardiovascular health, and lowered mortality rates due to cancer (colon, prostate, and breast), osteoporosis, and cognitive function.…”
Section: Compoundsmentioning
confidence: 99%
“…Tempe merupakan salah satu makanan tradisional Indonesia dengan bahan dasar kedelai yang difermentasi oleh jamur Rhizopus sp 79 . Nilai gizi suatu makanan dapat ditingkatkan melalui proses fermentasi, yaitu dengan meningkatkan vitamin, asam amino esensial, atau kandungan asam lemak, memfasilitasi detoksifikasi, dan menghilangkan faktor antinutrisional 49 .…”
Section: Tempe Kedelaiunclassified
“…Tempe kedelai memiliki kandungan isoflavon yang tinggi 79 . Isoflavon merupakan senyawa dari golongan flavonoid.…”
Section: Tempe Kedelaiunclassified